Healing Potential of Chromolaena odorata Extract: Modulation of Neutrophil, Macrophage, and Lymphocyte Response in Infected Wounds of Mus musculus - Melissa Abigail Yanis; Mirnasari Amirsyah; Anastasia Dessy Harsono (Postgraduate, University of Mataram, 2024)
Chromolaena odorata has been reported to possess antimicrobial, antibacterial, and anti-inflammatory properties that aid in wound healing. Previous studies demonstrated the significant effects of a 7.5% concentration of C. odorata extract on non-infected wounds. This study aims to investigate its impact on infected wound healing. An experimental study was conducted on 36 mice, divided into two groups. Partial-thickness wounds were created on the dorsal side of each mouse and contaminated with S. aureus (106 CFU/ml). Group 1 was treated with normal saline, while Group 2 was treated with C. odorata aqueous extract at 7.5%. Histopathological analysis was performed on days 3 and 5 to count neutrophils, macrophages, and lymphocytes. Results showed a significantly lower neutrophil, macrophage, and lymphocyte count in Group 2 compared to Group 1 (p < 0.05). On day 3 and 5, Group 2 had lower neutrophil counts (5.6 ± 1.8, 5.8 ± 0.6) compared to Group 1 (9.2 ± 5.2, 15.1 ± 3.9). Macrophage counts were also lower in Group 2 (6.9 ± 1.7, 1.9 ± 0.7) compared to Group 1 (3.7 ± 1.4, 4.3 ± 0.9). Lymphocyte counts followed a similar trend, with Group 2 having fewer lymphocytes on both days (p < 0.05). In conclusion, C. odorata aqueous extract at a 7.5% concentration demonstrates potential as a wound healing agent by reducing inflammatory cells in infected wounds.